The study of combustion characteristics of corn stalks and cobs via TGA-DTG-DSC analysis. (October 2019) - Wang, X D; Xue, J J; Zhu, Y J; Liu, C R; Hu, X Y; Liang, H; Dong, C Q
Abstract: To fully utilize the corn residuals, the combustion characteristics of corn stalks and corn cobs via TG-DTG-DSC (thermogravimetric-differential thermogravimetric-differential scanning calorimetry) were studied. The TGA, DTG and DSC curves are analysed and the combustible characteristics, burnout characteristics, comprehensive combustion characteristics are calculated to estimate the combustion characteristics of corn stalks and corn cobs. The results show the combustible ability of corn cobs is better than that of corn stalks. The ignition temperature of cobs is lower than that of stalks. The combustion rate of cobs is faster than that of stalks. However, the burnout characteristics of stalks are much better than that of cobs. The burnout temperature and time of stalks is higher and longer than that of cobs. The different combustion characteristic of stalks and cobs result from the difference of composition of stalks and cobs. The NIRS spectra also show the spectra of stalks and cobs are significantly different in the range of 1100-1300nm, where is the information of the C-H stretching vibration. In conclusion, it is better to co-combustion of corn stalks and cobs to improve the combustible and burnout characteristics, which will result in easier ignition and more stable combustion. The results of this study will provide guidance to the better utilization of biomass.